The Influence Of Financial Literacy And Digital Finance On Umkm Performance (Study On The Trade Sector In The Pamulang University Area) - Romadhona, Delia; Nuryani, Anum (Pascasarjana Universitas Pasundan, 2024)
This study aims to analyze the effect of Financial Literacy and Digital Finance on the Performance of MSMEs in the trade sector in the Pamulang University area. The method used in this study is a quantitative method. Data collection using questionnaires distributed directly to research objects. The population in this study were all MSME actors in the Pamulang University area as many as 112 MSMEs. The research sample was 88 MSMEs with a sampling method, namely simple random sampling. With data analysis that looks at descriptive statistical tests, classical assumption tests, correlation coefficient tests, simple linear regression tests, multiple linear regression tests, determination coefficient tests, and hypothesis tests. The results of the study show that Financial Literacy and Digital Finance have a positive and significant effect on MSME Performance partially. Simultaneously, Financial Literacy and Digital Finance also have a positive and significant effect on MSME performance together.